PENERAPAN PEMBELAJARAN AUDITORY INTELLECTUALLY REPETITION UNTUK MEREMEDIASI MISKONSEPSI SISWA TENTANG FLUIDA DINAMIS - Yuli Sri Pratiwi; Haratua Tiur Maria S; Syukran Mursyid (Universitas Tanjungpura, 2019)
AbstractThe aims of this research was to remediated of student’s misconceptions through the application of Auditory Intellectually Repetition (AIR) in fluid dynamics at SMA Negeri 5 Pontianak. One group pretest-posttest design was used as method of this research. Population of this research was all students of SMA Negeri 5 Pontianak. The samples was used intact group technique which the outcome is class of XI IPA 4 with 32 students. Diagnostic test was used as the instrument of this research, it’s consist of 9 multiple choice questions. Based on the data analysis, the mean percentage of student's misconception decreasing is 42,47%. McNemar statistic test result with dk = 1 and α = 5% showed >, this result showed that there is a significant change of the student’s conception. The effect size cohend’s of AIR in the remediation of misconception is 1,05 (high category). In conclusion, the remediation of misconception through application of AIR is capable to overcome student’s misconception. Keywords: remediation, misconceptions, Auditory Intellectually Repetition,fluid dynamics